Classification of Urban Solid Waste Collected with the Use of Ecobarriers in Watercourses in the Municipality of Caçapava do Sul, RS - Kemerich, Pedro Daniel da Cunha; Fernandes, Gabriel D’Avila; Forgiarini, Gabriel; da Silva, Leonardo Rosa; Vidal, Douglas Bitencourt (Anuário do Instituto de Geociências, 2023)
Urban solid waste is a serious problem in cities when disposed in inappropriate places or when there is a deficiency in its collection, which can cause several environmental problems. In periods of rain, these problems become more evident when these residues are transported to drainage networks and water courses, accumulating and creating obstacles to the flow, causing floods, floods, etc. In this regard, this work aimed to collect and classify urban solid waste in two water courses in the municipality of Caçapava do Sul, an ecological barrier made with recyclable materials called Ecobarrier, placed across water courses in order to retain floating waste that is transported by water. As a result, the vast majority of residues retained in the eco-barriers correspond to the category of organic matter, this is due to the vegetation around the water bodies studied, followed by the plastic, metal and textile category respectively. Thus, it can be seen that the presence of floating garbage in the water courses of the municipality partially reflects the lack of concern on the part of the population and governments with its effects on human and environmental health. It is in this context, to avoid the generation of floating waste, that the integration of public policies can play a fundamental role, with the help of environmental education.